Out of the blue : how animals evolved from prehistoric seas - Shreeve, Elizabeth; Preston-Gannon, Frann (Somerville, Massachusetts : Candlewick Press, 2021)
Simple text and illustrations trace the evolution of life on Earth, from the survival of microbes for billions of years on an ocean-covered planet through the Cambrian Explosion, the emergence of reptiles and the rise of mammals.
School Library Journal starred, April 2021
Kirkus Starred, April 2021
Includes bibliographical references.
3.9
K-3
Keywords: Evolution (Biology) -- Juvenile literature; Evolution (Biology).; Nonfiction picture books; Animals, Fossil -- Juvenile literature; Marine animals, Fossil -- Juvenile literature